The relationship between physical activity and Body Mass Index among medical students - Pearlie, Michelle Maydelaine; Lubis, Yolanda Eliza Putri; Delfian, Taufik (Jurnal Prima Medika Sains, 2024)
Preserving one's physical health and preventing diseases is of utmost importance, and leading a healthy lifestyle is essential. The absence of physical activity has been identified as a significant risk factor for obesity and chronic illnesses.This study aimed to establish an intricate relationship between physical activity level and Body Mass Index (BMI) among medical students. This analytical study used a cross-sectional design. Data were collected from October to December 2023. A total of 144 medical students enrolled at Universitas Prima, Indonesia participated in this study. Physical activity data were obtained using the International Physical Activity Questionnaire (IPAQ), whereas BMI was measured using the standard method of dividing weight in kilograms by the square of height in meters (kg/m²). Data analysis was performed using a One-Way ANOVA statistical test. The study findings revealed a significant difference (p < 0.05) between physical activity levels and BMI. Students in the light activity group had an average BMI of 28.57 kg/m², compared to 23.27 kg/m² for the moderate activity group and 21.66 kg/m² for the vigorous activity group. This indicates that physical activity plays a crucial role in determining BMI, with moderate- and vigorous-intensity activities associated with ideal BMI ranges. This study underscores the importance of physical activity in maintaining healthy weight and reducing the risk of obesity and associated chronic diseases. Promoting physical activity among university students can be an effective strategy for promoting their overall well-being.